2012
DOI: 10.1109/tnano.2011.2180735
|View full text |Cite
|
Sign up to set email alerts
|

PolyMethyl Methacrylate Thin-Film-Based Field Emission Microscope

Abstract: A field emission microscope (FEM) is a useful tool for investigating molecular surface structures. Conventional FEMs suffer from poor image contrast level and low sensitivities when low-energy electron beams are applied. In this article, a new anode material is employed to improve the FEM imaging performance. We demonstrate that the device has the capability of clearly capturing images of facet boundaries of crystal structures at the tip of a zinc oxide (ZnO) nanowire as defect sites on a Polymethyl methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For example, a PMMA layer was integrated on the anode of a vacuum diode device to image electrons emitted by DC field emission from ZnO nanowires. 35 Moreover, recently Volpe et al 36 and Dregely et al 37 have used PMMA and HSQ respectively to map the optical near-field of plasmonic Au nanoantennas. Volpe et al observed that PMMA decomposed within the plasmonic hotspots of Au nanorods illuminated at a resonant wavelength of 800 nm.…”
mentioning
confidence: 99%
“…For example, a PMMA layer was integrated on the anode of a vacuum diode device to image electrons emitted by DC field emission from ZnO nanowires. 35 Moreover, recently Volpe et al 36 and Dregely et al 37 have used PMMA and HSQ respectively to map the optical near-field of plasmonic Au nanoantennas. Volpe et al observed that PMMA decomposed within the plasmonic hotspots of Au nanorods illuminated at a resonant wavelength of 800 nm.…”
mentioning
confidence: 99%
“…The second is the study of electron emission patterns originating from molecular structures and nanostructures. Examples include patterns corresponding to the tip structures of nanotubes and nanowires, which change as the tip evolves during nanotube growth [9][10][11]. It is by combining the techniques of ultrafast emission and emission microscopy that Yanagisawa and colleagues have demonstrated that the emission patterns can be directly linked to specific molecular orbitals.…”
Section: Credit: Jst Prestomentioning
confidence: 99%
“…PMMA has been used in earlier works as an imaging layer for electrons. For example, a PMMA layer was integrated on the anode of a vacuum diode device to image electrons emitted by DC field emission from ZnO nanowires [299]. Moreover, recently Volpe et al [248] and Dregely et al [300] have used PMMA and HSQ respectively to map the optical near-field of plasmonic Au nanoantennas.…”
Section: Mapping Electron Emission On Materialsmentioning
confidence: 99%